2015
DOI: 10.1021/acs.macromol.5b00334
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Rapid Trimerization of Cyanate Ester in a Benzoxazine/Cyanate Ester Blend

Abstract: Blends of cyanate ester and benzoxazine have been independently studied by several researchers, and different reaction mechanisms were reported. Recently, we unexpectedly observe that gelation occurred in a 50 wt % methyl ethyl ketone solution of P-oda/BACY (1/1 mol/mol) blend after 24 h at 30 °C, in which P-oda is a 4,4′-oxyaniline/ phenol-based benzoxazine and BACY is a dicyanate ester of bisphenol A. Previous studies suggest that the rapid trimerization of cyanate ester in the blend is related to the ring-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Further, it was proposed that the ring-opened oxazine rings insert into the triazine rings to form cyanurates and isocyanurates, which then probably further react with oxazine rings to form other structures [ 176 ]. Wang et al [ 178 ] proposed the benzoxazine ring itself catalyzes both trimerization of cyanate ester and isomerization (cyanurate to isocyanurate) reactions upon heating. They showed the possibility of ROP for benzoxazine at 30 °C as evident from Figure 14 i.…”
Section: Classification Of Benzoxazine Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it was proposed that the ring-opened oxazine rings insert into the triazine rings to form cyanurates and isocyanurates, which then probably further react with oxazine rings to form other structures [ 176 ]. Wang et al [ 178 ] proposed the benzoxazine ring itself catalyzes both trimerization of cyanate ester and isomerization (cyanurate to isocyanurate) reactions upon heating. They showed the possibility of ROP for benzoxazine at 30 °C as evident from Figure 14 i.…”
Section: Classification Of Benzoxazine Monomersmentioning
confidence: 99%
“… ( i ) Digital images of a 50 wt% methyl ethyl ketone solution of PH-oda/BADCY (Bisphenol A dicyanate ester) (1/1, mol/mol): ( a ) freshly prepared solution, and the thermally treated solution at ( b ) 30 °C for 24 h, ( c ) 50 °C for 4 h and ( d ) 100 °C for 2 h [ 178 ]. ( ii ) Proposed catalytic mechanism of benzoxazine to the trimerization of cyanate ester solutions [ 178 ]. Copyright 2015.…”
Section: Figurementioning
confidence: 99%
“…The high reaction temperatures of MA groups, although might be reduced with Lewis base and Brønsted acid pendants, limit the developments of MA‐based thermosetting resins due to less processing convenience and high energy consumption. On the other hand, benzoxazine‐based thermosetting resins and their reactive blends with other thermosets have been widely reported. One drawback of the benzoxazine‐based resins is still high reaction temperatures, although it could be catalyzed with acidic compounds …”
Section: Introductionmentioning
confidence: 99%
“…From the DSC curve of pure cyanate ester in Figure 4, it can be observed that the curing temperature of pure cyanate ester was in the range of 270 to 320°C without adding catalyst. But Figure 3 showed a lower curing temperature, which can be related to the promotion of active phenolic hydroxyl generated from ring-opening of oxazine ring [29][30][31]. Moreover, with the introduction of CE, the temperature of first exothermic peak in prepolymers decreased, indicating that copolymerization occurred between oxazine ring and cyanate ester.…”
Section: Results and Discussion 31 Curing Behaviors Of A-ph/cementioning
confidence: 95%